THE CONVERGENCE OF EASE AND EXCELLENCE: GAUGING USER ADOPTION AND SYSTEM QUALITY IN IOT-ENABLED RECYCLING (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
This study evaluates an IoT-based system designed for junk and scrap trading, employing a dual approach that combines user acceptance and expert quality assessment. A purposive sample of 110 respondents (50 students, 50 employees, and 10 junkshop employees) participated in a survey based on the Technology Acceptance Model (TAM). Expert evaluators, selected based on qualifications in software engineering and system quality assessment, rated the system against ISO 25010 standards. TAM results indicated strong positive perceptions across all constructs, including perceived usefulness, ease of use, and willingness to adopt. Expert evaluation revealed consistently high ratings across ISO 25010 quality dimensions, although Functional Suitability showed significant differences (F = 4.703, p = 0.011), with junkshop employees rating it lower compared to students and employees. The study demonstrates practical efficiency gains, such as faster appraisal and more accurate counts of recyclable items, contributing to broader sustainability goals by reducing waste mismanagement. Findings highlight both behavioral acceptance and technical robustness as critical to adoption, emphasizing the need for refinements to align functionalities with frontline users’ needs. The integration of TAM and ISO 25010 offers comprehensive insights for future system development and supports the advancement of sustainable circular economy practices.
Keywords: IoT-enabled recycling; functional suitability; Technology Acceptance Model; ISO 25010; user adoption